Hubungan antara Kecemasan dan Kecanduan Internet dengan Insomnia pada Mahasiswa Yang Sedang Skripsi - M. Zuhdi Zainul Majdi; Sulastri Mulyana (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2023)
The purpose of this study was to determine the relationship between anxiety and internet addiction with insomnia in students who are doing their thesis. This study uses a non-experimental quantitative design. Taking the subject using purposive sampling. Respondents in this study were 40 people. Data collection uses 3 instruments; insomnia scale, internet addiction scale, anxiety scale. Data analysis used multiple linear regression with the help of SPSS. The results of this study indicate that there is a significant relationship between anxiety and internet addiction with insomnia in students who are doing their thesis. The higher the level of anxiety and internet addiction, the higher the level of insomnia experienced by students.